Information Security Threats on Social Network Sites: a Security Readiness and Mindfulness among IT and Non-IT Postgraduate Students - Moh. T. L. Ashafee, Somia; Haryani Zakaria, Nur; Mohamad Tahir, Hatim; Katuk, Norliza; Nizam Omar, Mohd (International Journal of Engineering and Technology, 2018)
The concept of security and privacy in Social Networks Sites (SNS) are becoming very popular and the number of users are increasing rapidly. These issues run from unapproved access to individual data to digital harassing. Past researchers have been applying alternate points of view including specialized tools and law to ponder protection and security issues. The issues of security and protection is by all accounts continuous. In perspective of the security dangers and protection issues of students utilizing SNS, this investigation embarks to analyst the security mindfulness, readiness towards digital assaults and security practices among IT and Non-IT postgraduate understudies. A total of 400 postgraduate students were studied utilizing a self-directed poll. The discoveries announced in this examination uncovered that IT understudies have altogether high security mindfulness and conduct when contrasted with Non-IT students. Be that as it may, there is no critical contrast between the readiness towards digital attacks of both IT and Non-IT students. This investigation exhibits that there is a critical connection between readiness towards digital attacks and security practices. The hypothetical and common-sense ramifications of this investigation feature the significance of security mindfulness and comprehension of specialized know how in seizing security assaults among SNS clients.Â Â